Indigenous Peoples' Cultural Property Claims Repatriation and Beyond - Kuprecht, Karolina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book analyses the legal aspects of international claims by indigenous peoples for the repatriation of their cultural property, and explores what legal norms and normative orders would be appropriate for resolving these claims. To establish context, the book first provides insights into the exceptional legislative responses to the cultural property claims of Native American tribes in the United States and looks at the possible relevance of this national law on the international level. It then shifts to the multinational setting by using the method of legal pluralism and takes into consideration international human rights law, international cultural heritage law, the applicable national laws in the United Kingdom, France and Switzerland, transnational law such as museum codes, and decision-making in extra-legal procedures. In the process, the book reveals the limits of the law in dealing with the growing imperative of human rights in the field, and concludes with three basic insights that are of key relevance for improving the law and decision-making with regard to indigenous peoples$1 (Bcultural property.s
Introduction -- Facts, Method and Basic Concepts -- National Cultural Property Repatriation Claims of the Native Americans -- International Cultural Property Repatriation Claims of Indigenous Peoples -- Requirements and Objectives for Appropriate Solutions -- Summarising Conclusion.
Keywords: Law; Humanities; Anthropology; Law; Human Rights; Cultural Heritage; Anthropology; Private International Law, International & Foreign Law, Comparative Law